Base de datos para las estimación de sedimentos en México - Salas Aguilar, Victor Manuel (Programa Mexicano del Carbono, 2019)
https://www.researchgate.net/publication/331101846_BASE_DE_DATOS_PARA_LA_ESTIMACION_DE_SEDIMENTOS_EN_SUBCUENCAS_DE_MEXICO_DATABASE_FOR_THE_ESTIMATION_OF_SEDIMENTS_IN_SUBCUENCAS_OF_MEXICO